DEVELOPMENT OF QUIZIZZ-BASED TEST QUESTIONS ON PRODUCTION COST CALCULATION MATERIAL - Puspitasari, Andini Eka; Gunawan, Hendri; Pratiwi, Nova (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
This research was developed to assist teachers in conducting evaluations and making the evaluation process enjoyable. The purpose of the research is to determine the validity, practicality, and potential test of student learning outcomes. This research was conducted at SMK Bina Sriwijaya Indonesia which is located at Jl. Mayjen HM Ryacudu No.24, 9/10 Ulu, Seberang Ulu I District, Palembang City, South Sumatra. The research was conducted using the Research and Development (R&D) method, which was combined with Sugiyono's development model. In this study, data collection techniques were used, namely observation, questionnaires, and test questions. The results of data analysis showed that quizizz-based test questions on production cost calculation materials received a validity score of 87% from material experts and 88% from media experts who were categorized as "Very Valid", the practicality test had a percentage score of 89% with the category "Very Practical", and the N-Gain results prove that there is a significant difference after using the product. Quizizz-based test questions on production cost calculation materials are proven to be valid, practical, and have a potential effect on student learning outcomes. This shows that quizizz can be an effective tool in learning evaluation.